2022
DOI: 10.2196/37777
|View full text |Cite
|
Sign up to set email alerts
|

Experiences With a Postpartum mHealth Intervention During the COVID-19 Pandemic: Key Informant Interviews Among Patients, Health Care Providers, and Stakeholders

Abstract: Background Maternal morbidity and mortality in the United States continue to be a worsening public health crisis, with persistent racial disparities among Black women during the COVID-19 pandemic. Innovations in mobile health (mHealth) technology are being developed as a strategy to connect birthing women to their health care providers during the first 6 weeks of the postpartum period. Objective This study aimed to inform a process to evaluate the barri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…education, reminder system Pilot mHealth programme (New Jersey, U.S.): text-based two-way messaging system for 6 weeks postpartum with daily six-item questionnaire. ‘Yes’ responses triggered telephone follow-up by provider [ 32 ] OGTT oral glucose tolerance test, U.S. United States …”
Section: What Strategies Have Been Trialled To Increase Postpartum At...mentioning
confidence: 99%
See 2 more Smart Citations
“…education, reminder system Pilot mHealth programme (New Jersey, U.S.): text-based two-way messaging system for 6 weeks postpartum with daily six-item questionnaire. ‘Yes’ responses triggered telephone follow-up by provider [ 32 ] OGTT oral glucose tolerance test, U.S. United States …”
Section: What Strategies Have Been Trialled To Increase Postpartum At...mentioning
confidence: 99%
“…More recently, the use of technology has allowed the opportunity to expand strategies beyond reminder-based messaging alone, for example to incorporate remote blood pressure monitoring [ 35 ], and education delivery [ 32 ]. Use of technology within the postpartum setting to specifically increase attendance rates has yet to be explored definitively particularly in high-income settings.…”
Section: What Strategies Have Been Trialled To Increase Postpartum At...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported the experiences of women in developed countries regarding mHealth intervention targeted at postnatal care [16,17]. However, while there has been a number of mHealth related studies in LMIC [18][19][20], there is paucity of data on the experiences of the end-users.…”
Section: Introductionmentioning
confidence: 99%
“…Hasil penelitian menyebutkan ada satu dari sembilan ibu paska lahir yang mengalami depresi postpartum (Shorey et al, 2018). Penyebab munculnya depresi postpartum diakibakan banyak hal seperti adanya kecemasan, ketidakberdayaan, peristiwa masa lalu, masalah kesehatan bayi, dan pengetahuan yang kurang (Beerli et al, 2022;Sadural et al, 2022;Slomian et al, 2017). Perkembangan teknologi informasi yang semakin berkembang pesat terutama di bidang medis melahirkan konsep inovatif dalam diagnosis dan penanganan teknis pasien, seperti telemedicine.…”
unclassified